EVALUASI PERKEMBANGAN BUMDES SYARI’AH USAHA BERSAMA DESA MAHATO SAKTI - Anissa Dwi Parwati; Ernawati (Fakultas Ekonomi Universitas Pasir Pengaraian, 2023)
BUMDes is a community economic institution that is managed directly by the village community and village government to obtain results and profits. The existence of BUMDes is very strategic which in the end BUMDes functions as a driving force for the villageeconomy and the welfare of the village community. The results of the BUMDes are not only used for business development but also for village development, empowering village communities, and providing assistance to the poor through grants, social assistanc e, andrevolving fund activities as stipulated in the Village Revenue and Expenditure Budget. The purpose of this study is the development of BUMDes Syariah Joint Venture Mahato Sakti Village in terms of its development classification. In this study using a descriptive quantitative approach. The population of this study is 700. The sampling technique used by the authors in this study is a non-probability sampling method, with the accidental sampling method, which is a method of taking sample sizes by chance by distributingquestionnaires to respondents or customers calculated using the slovin formula so as to obtain the number of samples is 200 people. The level of development of BUMDes is measured by the Ministry of Health version score: basic: 25 – 49, growing: 50 -74, developing: 75 - 85 and advanced: above 86. The data analysis technique uses descriptive statistics. The results of the study show that the development of BUMDes Syariah Joint Venture Mahato Sakti Village in terms of its development classification is in the developing category with a score of 82.1 with six assessment parameters that have been set by the Ministry of Villages is institutions, rules/legality, BUMDes business, administration, reporting and accountability, capital and assets and the impact of BUMDes on villagecommunities.